2021
DOI: 10.3389/pore.2021.598550
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ARID1A Expression as a Favorable Prognostic Factor in Early-Stage Grade 3 Endometrioid Endometrial Carcinoma Patients

Abstract: Introduction: High-risk patients with grade 3 endometrioid endometrial carcinoma (G3EEC) who require adjuvant therapy have not been clearly identified. Therefore, the current study aimed to investigate the prognostic impact of ARID1A, p53, and mismatch repair (MMR) protein expressions, previously reported as prognosticators in some gynecological cancers, in patients with early-stage G3EEC.Methods: A total of 67 patients with pathologically confirmed early-stage G3EEC diagnosed between 1997 and 2020 were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Owing to its low sensitivity, ARID1A does not appear adequate as a stand-alone diagnostic marker of premalignant EH, but it may be useful as a "rule-in" test for diagnosis of precancer, due to its excellent specificity. In agreement with our findings, ARID1A loss was reported to be associated with longer progression-free survival (P= 0.04) and that 7/9 of cases with recurrence in their study showed retained ARID1A expression (25) . Also, it was demonstrated that ARID1A mutations correlate with favorable survival in EEA using data from The Cancer Genome Atlas (44) .…”
Section: Combined Arid1a and Cd8+ Expression In Relation To Patient S...supporting
confidence: 92%
See 1 more Smart Citation
“…Owing to its low sensitivity, ARID1A does not appear adequate as a stand-alone diagnostic marker of premalignant EH, but it may be useful as a "rule-in" test for diagnosis of precancer, due to its excellent specificity. In agreement with our findings, ARID1A loss was reported to be associated with longer progression-free survival (P= 0.04) and that 7/9 of cases with recurrence in their study showed retained ARID1A expression (25) . Also, it was demonstrated that ARID1A mutations correlate with favorable survival in EEA using data from The Cancer Genome Atlas (44) .…”
Section: Combined Arid1a and Cd8+ Expression In Relation To Patient S...supporting
confidence: 92%
“…Also, it was demonstrated that ARID1A mutations correlate with favorable survival in EEA using data from The Cancer Genome Atlas (44) . A possible explanation for favorable prognosis of ARID1A loss in EEA is the relation of ARID1A loss with certain molecular subtypes of endometrial carcinoma those with MMR deficiency and POLE mutations that are considered a favorable prognostic factor in EEA (25) .…”
Section: Combined Arid1a and Cd8+ Expression In Relation To Patient S...mentioning
confidence: 99%
“…All IHC tests, including those for p53 (DO7, prediluted, Dako, Glostrup, Denmark), ARID1A (rabbit polyclonal, 1:2000, Sigma), PMS2 (EP51, prediluted, Dako), and MSH6 (EP49, prediluted, Dako), were performed as described in our previous study 21,22 . Furthermore, an IHC test for CTNNB1, the primary antibody of β‐catenin (clone14, 1:500; BD Bioscience), was performed in this study.…”
Section: Methodsmentioning
confidence: 99%
“…All IHC tests, including those for p53 (DO7, prediluted, Dako, Glostrup, Denmark), ARID1A (rabbit polyclonal, 1:2000, Sigma), PMS2 (EP51, prediluted, Dako), and MSH6 (EP49, prediluted, Dako), were performed as described in our previous study. 21 , 22 Furthermore, an IHC test for CTNNB1, the primary antibody of β‐catenin (clone14, 1:500; BD Bioscience), was performed in this study. The term “aberrant p53 staining pattern” refers to either a strong and diffuse nuclear staining pattern (>80% of carcinoma cells) or completely negative (“null pattern”) staining pattern of carcinoma cells, with staining of the adjacent nontumor cells serving as an internal positive control.…”
Section: Methodsmentioning
confidence: 99%
“…Among those, NSMP is the most heterogeneous group and the one for which novel biomarkers of risk stratification are urgently needed. To this aim, in the present study we have applied the aforementioned molecular classification to a cohort of high-risk ECs and further investigated the expression of additional markers with known prognostic potential in EC—estrogen (ER) and progesterone (PR) receptors [ 11 , 12 ], L1 Cell Adhesion Molecule (L1CAM) [ 12 , 13 , 14 , 15 ], Catenin Beta 1 (CTNNB1) [ 16 ], AT-Rich Interaction Domain 1A (ARID1A) [ 17 , 18 ], ki-67 proliferation index [ 19 ], and intratumoral immune cell infiltrate [ 20 ]—within the four molecular subgroups. Specifically, we analyzed the potential of those additional markers to further stratify the NSMP category, characterized by marked heterogeneous clinicopathologic features and prognosis.…”
Section: Introductionmentioning
confidence: 99%